Effect of by-pass and effluent recirculation on nitrogen removal in hybrid constructed wetlands for domestic and industrial wastewater treatment. (15th October 2016) - Torrijos, V.; Gonzalo, O.G.; Trueba-Santiso, A.; Ruiz, I.; Soto, M.
Abstract: Hybrid constructed wetlands (CWs) including subsurface horizontal flow (HF) and vertical flow (VF) steps look for effective nitrification and denitrification through the combination of anaerobic/anoxic and aerobic conditions. Several CW configurations including several configurations of single pass systems (HF + HF, VF + VF, VF + HF), the Bp(VF + HF) arrangement (with feeding by-pass) and the R(HF + VF) system (with effluent recirculation) were tested treating synthetic domestic wastewater. Two HF/VF area ratios (AR) were tested for the VF + HF and Bp(VF + HF) systems. In addition, a R(VF + VF) system was tested for the treatment of a high strength industrial wastewater. The percentage removal of TSS, COD and BOD5 was usually higher than 95% in all systems. The single pass systems showed TN removal below the threshold of 50% and low removal rates (0.6–1.2 g TN/m 2 d), except the VF + VF system which reached 63% and 3.5 g TN/m 2 d removal but only at high loading rates. Bp(VF + HF) systems required by-pass ratios of 40–50% and increased TN removal rates to approximately 50–60% in a sustainable manner. Removal rates depended on the AR value, increasing from 1.6 (AR 2.0) to 5.2 g TN/m 2 d (AR 0.5), both working with synthetic domestic wastewater. On real domestic wastewater the Bp (VF + HF) (AR 0.5 and 30% by-pass) reached 2.5 g TN/m 2 d removal rate. Effluent recirculation significantly improved the TN removal efficiency and rate. The R(HF + VF) system showed stable TN removals of approximately 80% at loading rates ranging from 2 to 8 g TN/m 2 d. High TN removal rates (up to 73% TN and 8.4 g TN/m 2 d) were also obtained for the R(VF + VF) system treating industrial wastewater. Highlights: Single pass systems showed TN removal below 50% at 0.6–1.2 g TN/m 2 d. 30–50% by-pass in Bp(VF + HF) system increased TN removal up to 60%. Removal rates (1.6–5.2 g TN/m 2 d) highly depended on HF/VF area ratio in Bp(VF + HF). Recirculation increased stability and TN removal rates up to 80% and 8 g TN/m 2 d. Recirculating R(VF + VF) system efficiently treated an industrial effluent of 4 g COD/L.